Role of Betaine in Transmethylation Reactions in the Barley Plant - Sribney, Michael (My University, 1953)
The role of the labile methyl groups of betaine in the transmethylation reactions in the barley plants was investigated using carbon-14 methyl labelled betaine. The N-methyl groups of N-methyl tyramine, hordenine and choline were found to arise from betaine. Betaine was also administered to castor bean seedlings and the alkaloid ricinine Isolated. It was found that Its N- and 0- methyl groups did not arise from betaine methyl. The origin of the methylenedioxy and N-methyl groups of the alkaloid protopine was also investigated by the tracer technique. Carbon-14 methyl labelled L- methionine, carbon-14 methyl labelled choline and carbon- 14 labelled sodium formate were fed to Dicentra species and the extent and position of labelling of the protopine molecule determined by degradation
Origin of the Methylenedioxy Groups of the Alkaloid Protopine
Keywords: Methylenedioxy Groups, Betaine, Transmethylation, Barley, Alkaloid Protopine